2006
DOI: 10.1111/j.1744-7909.2006.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Preliminary Analysis of Several Centromere‐associated Bacterial Artificial Chromosome Clones from a Diploid Wheat Library

Abstract: Although the centromeres of some plants have been investigated previously, our knowledge of the wheat centromere is still very limited. To understand the structure and function of the wheat centromere, we used two centromeric repeats (RCS1 and CCS1-5ab) to obtain some centromere-associated bacterial artificial chromosome (BAC) clones in 32 RCS1-related BAC clones that had been screened out from a diploid wheat (Triticum boeoticum Boiss.; 2n=2x=14) BAC library. Southern hybridization results indicated that, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We have also isolated two clones associated with wheat centromeres from the BAC library of Triticum boeoticum. One contains both centromeric and dispersed multi-copy elements, whereas a second has been found to hybridize in situ specifically to the centromeric regions of wheat (Chen et al 2002;Liu et al 2006). We report here the complete sequence of these two BAC clones and reveal that centromeric/pericentromeric sequences have evolved dynamically during speciation and allopolyploidization in wheat and its relatives.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We have also isolated two clones associated with wheat centromeres from the BAC library of Triticum boeoticum. One contains both centromeric and dispersed multi-copy elements, whereas a second has been found to hybridize in situ specifically to the centromeric regions of wheat (Chen et al 2002;Liu et al 2006). We report here the complete sequence of these two BAC clones and reveal that centromeric/pericentromeric sequences have evolved dynamically during speciation and allopolyploidization in wheat and its relatives.…”
Section: Introductionmentioning
confidence: 81%
“…Using the cereal centromeric universal repetitive sequence RCS1 ) and the cereal centromeric sequence CCS1 (Aragón-Alcaide et al 1996) as probes, 28 centromere-associated BAC clones were identified out of 3,072 clones screened (Chen et al 2002;Liu et al 2006), two of which (TbBAC5 and TbBAC30) were selected for detailed analysis. Based on their NotI, PmeI, SwaI, and PacI restriction fingerprints, their insert sizes were estimated to be 90 kb and 83.5 kb, respectively.…”
Section: Bac Library and Clone Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the genomic in situ hybridization (GISH) procedures as described by Cai et al (1998) and Liu et al (2006) Seeds were germinated in Petri dishes at 22°C for about 24 h. Roots of 1 to 2 cm in length were collected and pretreated in ice water for 20 to 24 h. After pretreatment, the roots were fixed in a 3:1 mixture of ethanol and acetic acid for 48 h at room temperature. To prepare the slide, root tips were transferred into 1% acetic carmine for 2 to 3 min and then root tips were squashed in 45% acetic acid under a cover glass.…”
Section: Methodsmentioning
confidence: 99%
“…The in situ hybridization (ISH) technique, developed more than 30 years ago (Gall and Pardue ; John et al ), has proved to be a powerful technique in cytological biology studies. Jiang and Gill () stressed florescent in situ hybridization (FISH) as one of the most important techniques in plant molecular cytogenetic research, because it allows DNA sequences to be mapped directly on chromosomes (Cheng et al , ; Dai et al ; Liu et al ; Jiang and Bikram ; Tang et al ). Genomic in situ hybridization (GISH) is one of the most effective methods to obtain integrated information of DNA biology on genomic chromosomes, and is therefore powerful in its ability to provide data on genomic evolution and specific relationships (Tan et al ; Liu et al ; Zhou et al ).…”
Section: Introductionmentioning
confidence: 99%